Clinical Pattern of Limb Loss in Electrical Burn Injuries: Limb Loss in Electrical Burn Injuries - Sanober, Aamna; Siddique, Afaq Saleem; Shaikh, Shahzad; Irshad, Samra; Ahsan Qureshi, Pir Naveed Ahmed; Sangrasi, Hira; Memon, Rabia (Pakistan Journal of Health Sciences, 2025)
Electrical burn injuries are severe and often lead to significant morbidity, including amputations, especially in high-voltage cases. These injuries commonly occur in occupational settings and can result in prolonged hospitalization and complications. Studying clinical patterns in electrical burn injuries is crucial to identifying risk factors, improving early interventions, and guiding effective treatment plans. Objective: To analyze the clinical pattern of amputation in electric burn patients at Burns Unit, Liaquat University Hospital, Hyderabad. Methods: This prospective observational study was conducted at Liaquat University Hospital, Hyderabad, from Nov 2023 to May 2024. A total of 84 patients, of all ages and both genders who presented with electrical burn injuries were included. While those with scald burns, dry flame burns, contact burns, thermal burns, or uncontrolled diabetes mellitus were excluded. Data collection involved recording demographic details and clinical parameters like the type of burn, total body surface area affected, cause and place of burn, duration of hospital stay, mortality rate and surgical intervention. Results: Among all, 54.8% (n=46) required amputations, with 35.7% involving a single limb and 19% multiple limbs. Upper limb amputations were more common (60.9%) compared to lower limb amputations (39.1%), with an 11.9% mortality rate. High-voltage burns were significantly associated with severe total body surface area involvement, prolonged hospitalization, fasciotomies, and multiple limb amputations. Conclusion: It was concluded that the study reported a high frequency of limb loss (due to amputation) i.e. 54.8% (n=46) among patients with electric burn.